SALCER´s Project - Carlos Pérez; Bosco Espinó (International Journal of Interactive Multimedia and Artificial Intelligence, 2009)
SALCER (in Spanish: Sistema de Asesoramiento y Localización de Centrales de EnergíaRenovables) could be translated as Counseling and Location of Renewable Energy Power Station´s System. Its objective is to develop a system capable of finding the most suitable place for the construction of renewable power stations, taking into account such things as: budget, topography, amount of energy needed, among others. The most relevant aims of the project are: study of a certain variety of renewable energy technologies, designing an accurate topology system, restraining decisions to demand forecasts and finally performance of an energy plan for a specific region